Optimum corrosion performance using microstructure design and additive manufacturing process control - Parisa Moazzen; Ayda Shahriari; SeyedAmirReza Shamsdini; Payam Seraj; Foroozan Forooghi; Yahya Aghayar; Sajad Shakerin; Mackenzie Remington Purdy; Mohsen Mohammadi (npj Materials Degradation)
Abstract Compatibility of traditional metallic alloys, particularly 316 L stainless steel, with additive manufacturing (AM) processes, is essential for industrial applications. This involves manipulating process parameters to design microstructures at various length scales, achieving desired properties for high-performance components. In this study, a hierarchical design approach was used for LPBF 316 L parts, achieving cell sizes of 400 to 900 nm confined within grains of 40 to 60 μm. Findings showed that varying scan strategies with constant energy input produced high-density components, with the smallest grain and cell size achieved in the continuous scan strategy. In addition, equations were developed to connect energy density with grain size for LPBF-316L, highlighting optimal scanning strategies. Furthermore, the correlation between microstructural features and corrosion behavior, focusing on electrochemical properties, was explored by adjusting key LPBF process parameters. The results suggested a Hall-Petch relationship between grain size and corrosion rate, indicating that smaller grains and cells reduce corrosion rates by affecting electrochemical behavior.